2010
DOI: 10.1038/ijo.2010.134
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity and insulin resistance are independent predictors of the presence of non-cirrhotic NAFLD-related portal hypertension

Abstract: Introduction: We previously demonstrated in an animal model that steatosis, in the absence of fibrosis, induces a significant rise in portal pressure, indicating substantial changes in liver hemodynamics. As assessment of portal pressure is an invasive procedure, non-invasive parameters are needed to identify patients at risk. Aims: To study the portal pressure in nonalcoholic fatty liver disease patients and to identify factors that are possibly related to steatosis-induced changes in liver hemodynamics. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 47 publications
6
52
0
Order By: Relevance
“…In addition, HOMA-2 index, together with prothrombin time, were the only independent predictors for the presence of CSPH. These findings suggest that IR may play a role in the progression of the chronic liver disease at the earlier stages, as it has already been suggested in patients with nonalcoholic fatty liver disease (16), where the presence of IR was associated with the presence of mild PH (in that study, all patients had HVPG Ͻ 10 mmHg). Interestingly, our data, including patients with more severe PH, show that, once CSPH has developed, the correlation between HOMA-2 index and HVPG is lost.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, HOMA-2 index, together with prothrombin time, were the only independent predictors for the presence of CSPH. These findings suggest that IR may play a role in the progression of the chronic liver disease at the earlier stages, as it has already been suggested in patients with nonalcoholic fatty liver disease (16), where the presence of IR was associated with the presence of mild PH (in that study, all patients had HVPG Ͻ 10 mmHg). Interestingly, our data, including patients with more severe PH, show that, once CSPH has developed, the correlation between HOMA-2 index and HVPG is lost.…”
Section: Discussionsupporting
confidence: 82%
“…Thus it has been suggested that IR has a negative impact on the response rates to interferon-based therapy in chronic hepatitis C virus infection (19) and that IR could be a predictor of the presence of PH in patients with nonalcoholic fatty liver disease (16). Furthermore, a recent published clinical study has suggested that IR is able to independently predict the presence of gastroesophageal varices in cirrhosis (11).…”
mentioning
confidence: 99%
“…Several studies in Western counties and Japan found that both the AST/ALT ratio and insulin resistance were important risk factors for the severity of NAFLD (20)(21)(22)(23)(24). Because the severity of NAFLD is apparently due to visceral fat accumulation (12,24), the negative correlations observed between the AST/ALT ratio and insulin resistance with the FSSG in the present study suggested that the relationship between the BMI and GERD symptoms may also be dependent on the visceral fat accumulation in subjects with NAFLD.…”
Section: Discussionsupporting
confidence: 53%
“…Both cohorts enrolled bariatric surgery patients. The third cohort was sampled in Antwerp in Belgium, and enrolled patients presenting at the obesity clinic for an overweight problem [21]. In all three cohorts, patients were excluded if they were reported to consume more than 20 g of alcohol per day.…”
Section: Methodsmentioning
confidence: 99%